General Didactic Principles of Pedagogical Technologies - Tilavoldiev.Sh; Madaliev.R. (Zien Journals, 2022)
This article deals with modern innovative technologies of teaching and their general didactic principles.
Keywords: The principle of unity; the principle of fundamentalism; the design of the educational process; the principle of active approach